2023
DOI: 10.1002/sres.2935
|View full text |Cite
|
Sign up to set email alerts
|

Managerialization, professionalization and firm performance in family business: A Systems Thinking perspective

Abstract: This paper proposes a systemic model on the intertwined relations among managerialization, professionalization and firm economic performance, considering both business‐ and family‐specific features and issues. It sheds light on the role that, in the family business, the firm economic performance may play in favouring a positive development of both the business and the family itself. It aims at understanding how, in family businesses, the firm managerialization and professionalization may represent relevant dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Although the field started with a simplified interpretation, as hiring non-family managers are a sufficient way of professionalizing the business (Klein & Bell, 2007;Zhang & Ma, 2009) recent studies showed that it is only a particular element of the development of family firms, and it consist many more elements, such as governance (Suess, 2014), strategic planning (Songini, 2006) formal human resource systems (Madison et al, 2018), cultural (Camfield & Franco, 2019), financial systems (Hiebl & Mayrleitner, 2019), decision-making (Basco, 2013) socio-emotional wealth (Gomez-Mejia et al, 2011) performance (Chang & Shim, 2015;Songini, Armenia, Morelli & Pompei, 2023) and business family (Polat, 2021) aspects.…”
Section: Contributions Of Chapter II a Systematic Literature Review O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the field started with a simplified interpretation, as hiring non-family managers are a sufficient way of professionalizing the business (Klein & Bell, 2007;Zhang & Ma, 2009) recent studies showed that it is only a particular element of the development of family firms, and it consist many more elements, such as governance (Suess, 2014), strategic planning (Songini, 2006) formal human resource systems (Madison et al, 2018), cultural (Camfield & Franco, 2019), financial systems (Hiebl & Mayrleitner, 2019), decision-making (Basco, 2013) socio-emotional wealth (Gomez-Mejia et al, 2011) performance (Chang & Shim, 2015;Songini, Armenia, Morelli & Pompei, 2023) and business family (Polat, 2021) aspects.…”
Section: Contributions Of Chapter II a Systematic Literature Review O...mentioning
confidence: 99%
“…Although professional managers are not the only way to develop the organization, they can bring new expertise and knowledge the company may not possess (Fabel et al, 2022). The integration of external managers can result in tangible benefits such as reducing the opportunistic behavior of family members (Songini et al, 2023) and an increase in financial performance. The study provided practical implications for family business owners and managers.…”
Section: Contributions Of Chapter II a Systematic Literature Review O...mentioning
confidence: 99%